Are contingencies vs provisions in different cultures as expected or not? Evidence with UK and Portugal - Trabucho, P.; Lopes, A.I.; Reis, L. (EAA 39th Annual Congress (European Accounting Association) - Presented Papers, 2016)
This paper uses culture to explore the extent to which both provisions and contingenciesare differently recognized and disclosed by companies of different environments and toexamine whether those difference are associated with the market value of those companies. Our results do not confirm the expectation for higher recognition in Portugal or a preference for disclosure in UK as suggested for high secrecy (vs. transparency) and high conservatism (vs. optimism) in countries with high (vs. low) uncertainty avoidance. Furthermore, we find that provisions and contingencies have a negative association with share prices - yet only statistically significant for the later - but when in presence of a risk committee on the board of directors, investors place a similar trust to both recognized and disclosed items assuming less creative accounting practices.